Development of History Learning E-Comics Based on Contextual Teaching And Learning to Improve Learning Outcomes of Class XI Students of SMA N 14 Bandar Lampung - Mayasari, Dian; Yulianti, Dwi; Sinaga, Risma Margaretha; Herpratiwi, Herpratiwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
In today's global era, learning history faces great challenges and is required to contribute to further developing awareness of nation and homeland for students. Lack of understanding of the history and culture of the nation, such as students who do not understand the history and culture of their nation tend to be difficult to develop an attitude of nationalism, especially the declining learning outcomes of history. The challenge for history teachers to follow up on the decline in learning outcomes is to utilize information and communication technology to bridge the problem of declining learning outcomes in class XI SMA country 14 Bandar Lampung by developing CTL-based history learning e-comics media. This study aims to 1) analyze the potential and conditions, 2) know the development process, 3) know the effectiveness and 4) analyze the attractiveness of the development of e-comic media based on contextual teaching and learning to improve the learning outcomes of class XI history at SMA country 14 Bandar Lampung. This research is a development research (R&D) using the ADDIE approach, data collection techniques using Observation, Interview Questionnaires and tests, the sample used in this study amounted to 30 students of class XI SMA country 14 Bandar Lampung, which were randomly selected. The results of the study are known 1) Potential and development conditions Based on the decline in student learning outcomes, the need for digital-based media with the context of involvement from students as learners. 2) The results of the validation of media experts, material experts, design experts, small groups, practitioners and implementation in large groups, show that the development of e-comic media for learning history based on contextual teaching and learning is feasible to be implemented in history learning. 3) The effectiveness of the development of CTL-based history e-comics received a fairly effective response with an N-Gain value of 68.35, and had an effect on improving student learning outcomes with a value of 0.003 <0.005 4) The attractiveness of product development can be classified as interesting with an average respondent response of 86.00%.